Prevalence of Anxiety and Depression and Their Psychosocial Correlates among Women Receiving Antenatal Care: A Cross-Sectional Study - Naeem Amjad, Ashfaq Ahmad, Ghulam Shabir Shaikh, Omar Murtaza Sheikh, Qamoos Razzaq, Areeb Gohar (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To determine the prevalence of anxiety and depression among women attending antenatal care and to identify associated psychosocial factors. Methods: A cross-sectional study was conducted at a Department of Psyciatry, Shahida Islam Medical College, Lodhran, from January to August 2023. A total of 200 pregnant women in their second and third trimesters were selected through convenience sampling. Depression and anxiety were assessed using the Patient Health Questionnaire-9 (PHQ-9) and Generalized Anxiety Disorder-7 (GAD-7), respectively. Psychosocial factors including marital status, education level, employment, income, social support, and history of mental illness were evaluated. Data were analyzed using SPSS version 26.0. Results: The prevalence of antenatal depression was 23% (n=46), and anxiety was 30% (n=60). Significant correlates of depression included low education (p<0.05), low income (p<0.01), and lack of social support (p<0.05). Anxiety was significantly associated with low income (p<0.01), lack of social support (p<0.05), and history of mental illness (p<0.05). Conclusion: Antenatal depression and anxiety are prevalent among pregnant women attending antenatal care. Socioeconomic factors and lack of social support are significant contributors. Addressing these factors may help in the development of targeted interventions to improve maternal mental health. Keywords: Antenatal depression, anxiety, psychosocial factors, prevalence, maternal mental health